Economic regulation: Recentralisation of power or improved quality of regulation? - Paul K. Gorecki (The Economic and Social Research Institute (ESRI), 2011)
The October 2009 Government Statement on Economic Regulation issued proposes a number of sensible reforms that are likely to improve regulatory performance in energy, airports, telecommunications, postal services and transport. However, the Government Statement also proposes to reduce the independence of regulators by holding them to account through a whole series of additional mechanisms, some of which are informal and lack transparency, while at the same time instructing regulators to take into account evolving/current - possible transient - priorities. There are good reasons for preserving and strengthening rather than undermining regulatory independence. For example, it facilitates investment in long-lived assets with a large element of sunk or irrecoverable investment, a common characteristic of network sectors. The Government Statement's unexplained move to reduce regulators' independence finds no support in either the government commissioned background report prepared by the Economic Intelligence Unit, Review of the Regulatory Environment in Ireland, or recent European Union legislation on energy and telecommunications regulation. Indeed, these sources are strongly in favour of regulatory independence. Two, not necessarily mutually exclusive explanations, for reducing regulatory independence are discussed: to remove an anomaly in the Irish political system; and, to assist in the delivery of social partnership. The paper concludes by arguing that some thought might be given to public consultation of the reforms in the Government Statement prior to further implementation.
Keywords: 330; regulation; independence; economic regulators; accountability; infrastructure sector; Government Statement on Economic Regulation